Determination of the price in the fresh fruit market: case of pears - Giacinti, Miguel Angel; Valenciano, Jaime de Pablo; Pires Manso, José Ramos (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2020)
This document aims to evaluate the determinants of the price of pears in the international fresh fruit market, from an innovative vision in a complex world. The panel data methodology was applied. The variables considered were the different prices (CIF/kg) of pear, apple and stone fruits, their per capita consumptions, real per capita income, consumer price indexes and real exchange rates. Pear consumption responds especially to apple consumption, but also to prices of apples and peaches, real per capita income, consumer price indexes and countries’ exchange rates. This might imply improving commercial efficiency in international trade, effective budgets in price formation, and giving new impetus to studies on the price of fruits and foods with a new vision. Highlights Pears’ price (CIF) is determined by the number of imported pears and apples; also for import prices of other fruits such as apples, peaches and nectarines. Panel data models is a novelty in this kind of articles. The panel integrates the yearly CIF imported prices (period 1990-2015) from 18 countries, the main world importers in the international demand for fresh pears. This research changes the paradigm in the fresh pear business, with the disclosure of this article. The paper fills a gap in the literature on international worldwide fruit commerce.